Predictive value of cardiac magnetic resonance mechanical parameters for myocardial fibrosis in hypertrophic cardiomyopathy with preserved left ventricular ejection fraction - Hou, Xian; Xiong, Xing; Li, Xia; Bi, Jianhua; Xu, Gaofeng; Wang, Yining; Jiang, Shu (Frontiers in Cardiovascular Medicine, 2022)
Objective: Myocardial fibrosis leads to systolic dysfunction in hypertrophic cardiomyopathy (HCM) patients. This study aims to investigate the relationship between cardiac magnetic resonance mechanical parameters for evaluating the left ventricular function in HCM with preserved left ventricular ejection fraction (LVEF ≥50%) and the association between myocardial fibrosis defined by late gadolinium enhancement (LGE). Methods: This study was a retrospective analysis of CMR images of 93 patients with HCM with preserved ejection fraction (HCMpEF) and 96 controls diagnosed by cardiac magnetic resonance (CMR) at our hospital from July 2019 to January 2022. The myocardial contraction fraction (MCF) was calculated, and myocardial mechanical parameters, including global myocardial longitudinal strain (GLS), circumferential strain (GLS), and myocardial strain (GLS), were obtained by tissue tracking and LGE quantitative modules of dedicated software, respectively. The correlation between myocardial strain and LGE was analyzed, and a multivariate logistic regression model was developed to discuss the risk predictors of LGE. Results: Compared to the control group, the left ventricular mechanical parameters GLS (-13.90±3.80% versus -18.20±2.10%, p<0.001), GCS (-16.62±3.50% versus -18.4±2.69%, p<0.001), GRS (28.99±10.38% versus 33.02±6.25%, p<0.01) and MCF (64±16% versus 99±18%, p<0.001) were found significantly lower in HCM group. Moreover, even in LGE-negative HCM patients, GLS (-16.3±3.9%) and MCF (78±19%) were significantly lower compared to the control group. Left ventricular GLS (OR=1.61, [1.29,2.02], p=0.001) and MCF (OR=0.90, [0.86,0.94], p=0.001) independently predicted myocardial late gadolinium enhancement(LGE). Conclusions: In participants of HCM with preserved ejection fraction, the early onset of reduced left ventricular GLS and MCF in patients with HCMpEF may provide new evidence for evaluating impaired myocardial systolic function. The reduction of myocardial mechanical indexes may reflect the presence and extent of myocardial fibrosis, and the more significant the reduction, the more severe the myocardial fibrosis; GLS and MCF may be ideal predictors for LGE.